(untitled) (The Strategic Review for Southern Africa, 2020)
In the first of two Research Articles, diaspora in a sub-regional context is the focus of the micro-study by Saint José Inaka. His analysis of the political clashes between militant and non-militant oriented. Congolese factions in Pretoria draws attention to a hitherto largely unknown phenomenon. The fights between grassroots activists relating to differences in political support in the Democratic Republic of the Congo have since the 2000s expanded into the local arena of the South African capital. Until then mainly a domain of middle classes and elites operating transnationally, the dividing line is less between those for or against the Kabila government than those for or against the use of violence. According to Inaka, Pretoria’s leniency towards the militant combattants allows them to limit the activities of those preferring peaceful means in support of change at home. Interestingly, the author submits that being exposed to the South African democracy has the impact of setting an example and reference point for how Congolese would like to be governed in their home country.